2012
DOI: 10.4021/jnr98w
|View full text |Cite
|
Sign up to set email alerts
|

Using Assistive Robotic Technology in Motor Neurorehabilitation After Childhood Stroke

Abstract: An intracranial haemorrhage resulted in severe motor impairment in the right upper limb in a previously physically-active young adolescent. Robot-assisted therapy was implemented over the course of 9 months to reduce motor impairment in the affected right upper limb. Robot-assisted therapy consisted of twice weekly sessions containing repetitive and progressively intense practice of hand grasping and arm reaching. The amount of assistance offered by the robot during grasping and reaching was adaptive such that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…They showed that, at the end of the training, the child decreased muscle tone, improved upper limb coordination and quality of movement while the strength remained the same, concluding that these outcomes were similar to those obtained after conventional occupation therapy combined with injections of BTX-A. Moreover, Turner et al [79] confirmed also the benefits of using robotic therapy in children affected by stroke. More specifically, they compared the reactions to InMotion2 robotic training of pediatric stroke patients with those of adult stroke population undergoing early robotic-assisted therapy.…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 71%
See 1 more Smart Citation
“…They showed that, at the end of the training, the child decreased muscle tone, improved upper limb coordination and quality of movement while the strength remained the same, concluding that these outcomes were similar to those obtained after conventional occupation therapy combined with injections of BTX-A. Moreover, Turner et al [79] confirmed also the benefits of using robotic therapy in children affected by stroke. More specifically, they compared the reactions to InMotion2 robotic training of pediatric stroke patients with those of adult stroke population undergoing early robotic-assisted therapy.…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 71%
“…Such three parameters are not only used to trigger robotic assistance, but also constantly measured to continuously modulate the robotic assistance according to child's performance and to make the rehabilitation adaptive and progressive. In particular, we quote 7 clinical studies involving this device [14,21,26,[76][77][78][79][80]. In one study [76], the robot was used to show the different responses of healthy children and pediatric patients to perturbing force fields: specifically, healthy subjects tend to learn to compensate for perturbed forces and consequently predict the force field; in contrast, children affected by weakness and spasticity due to CP, show a limitation of brain capacity to calibrate the sensorimotor system.…”
Section: Robotic Protocols For Upper Limb Rehabilitationmentioning
confidence: 99%
“…Rather combinations will provide a highly individualized training that is delivered in a repetitive and standardized fashion, for example tDCS and robot-mediated therapy ( 63 ). This will produce robot-based assessment measures that are comparable across patients with different motor disorders or at different time points of their lifespan (e.g., childhood vs. adult; ( 118 )) in the clinic and at home ( 119 ).…”
Section: Discussionmentioning
confidence: 99%